(untitled) (Annals of the University of Bucharest. Philosophy Series, 2025)
In this essay, I shall use Hadot’s critical framework for considering the uneasy modern relationship between philosophy and the Christian spiritual tradition, rooted as it is in the ancient forms of spiritual exercise. I will begin with a brief sketch of this relationship, paying particular attention to some ways that Christian spirituality influenced philosophy in early modernity. From there, I shall turn to the work of Bernard Lonergan in order to develop a proposal for a contemporary spirituality of discernment as a philosophical practice. Lonergan, a Jesuit trained in the Spiritual Exercises of Ignatius of Loyola, built his philosophical project on the template of those exercises, inviting people to practices of self-appropriation for the purpose of exploring how discernment in a community can transform societies, reversing decline and promoting patterns of growth. Lonergan’s method, I shall argue, offers a way of coming to understand the spirituality of discernment as a form of philosophical practice that heals the problems that Hadot diagnoses in modern philosophy.